CHOOSING THE APPROPRIATE DATABASE TYPE: A COMPARISON OF SQL, NOSQL, AND NEWSQL - BABUCEA ANA-GABRIELA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2024)
Databases are data collections organized for easy access and management, available simultaneously to multiusers. Access to the data can be controlled through various permissions, ensuring that users have the appropriate level of access based on their roles. This structure not only enhances data security but also improves collaboration among users, making it easier to share and analyze information efficiently. Databases are controlled through database management systems (DBMS) that allow users to add, modify, delete, locate, and view database data using specific languages provided in most database management software packages. The ability to query the database for particular information is the most powerful capability of any database management system. If we mean that databases have evolved to facilitate tasks such as searching, sorting, or reporting data and updating it based on user requirements, these tasks may be simple in essence, but when vast volumes of data are handled that are frequently accessed by multi users or stand-alone systems, the databases themselves become quite complex. This paper aims to compare the different database systems (SQL, NoSQL, and NewSQL), respectively, and the database models implemented by them from the perspective of the characteristics, similarities, and differences, as well as the advantages and disadvantages of their use in a concrete situations. Since each database type has advantages and disadvantages based on the particular context of use, selecting a database type is never simple and always necessitates a thorough examination of the application requirements and long-term benefits. This paper concentrated on evaluating the three main database types, SQL, NoSQL, and NewSQL, by comparing their essential features, assessing their benefits and limitations, and exploring their most suitable applications across various use cases. The study's conclusions could help choose the best database based on the business process requirements for the enterprise's tasks.